The recipe for peace: from Colombian ajiac to good coffee. Tests of conviviality and new coexistence - Pezzini, Isabella (E|C, 2020)
During the difficult Colombian national pacification project, signed starting from 2016 with an agreement between President Juan Manuel Santos and the revolutionary groups FARC-EP, the revaluation of Colombian cuisine has taken on a prominent place. It is an example of a "politics of taste" interesting for semiotic analysis and for comparison with other situations in which the conviviality conveyed by food and its preparation is exploited for more far-reaching cultural operations. In particular, this paper will focus on the image of coffee in the Colombian culture.